Construction of CII-Specific CAR-T to Explore the Cytokine Cascades Between Cartilage-Reactive T Cells and Chondrocytes - Liu, Xiaolong; Zhao, Jun; Shi, Ce; Liu, Zhiyu; Shen, Hongtao; Dang, Junlong; Li, Yang; Yang, Dongguang; Wei, Jia; Kang, Liqing; Zhou, Jin; Cao, Fenglin; et al. (Frontiers in Immunology, 2020)
Cytokine cascades exist in many autoimmune disorders which amplify and sustain the autoimmune process, and lead to chronic inflammatory injury to the host tissues. Increasing evidence indicates that chondrocytes can interact with T cells, which may be a crucial event in inflammatory arthritis. To address the reciprocal influences of cartilage-reactive T cells and chondrocytes, we constructed cartilage-reactive T cells by developing a type II collagen-specific chimeric antigen receptor (CII-CAR). An in vitro co-culture model of CII-CAR-T cells and fresh cartilage was developed, in which CII-CAR-T displayed specific proliferative capacity and cytokine release against fresh cartilage samples, and chondrocytes could respond to CII-CAR-T cells by secreting IL-6. The proposed model will help us to explore the possible cytokine cascades between cartilage-reactive T cells and cartilage.